An AGAMOUS-like factor is associated with the origin of two domesticated varieties in Cymbidium sinense (Orchidaceae). Issue 1 (1st September 2018) - Su, Shihao; Shao, Xiaoyu; Zhu, Changfa; Xu, Jiayin; Tang, Yuhuan; Luo, Da; Huang, Xia
Abstract: Cymbidium has been artificially domesticated for centuries in Asia, which produced numerous cultivated varieties. Flowers with stamenoid tepals or those with multiple tepals have been found in different species of Cymbidium ; however, the molecular basis controlling the formation of these phenotypes is still largely unknown. Previous work demonstrated that AGAMOUS/AG lineage MADS genes function in floral meristem determinacy as well as in reproductive organs development in both dicots and monocots, indicating a possible relationship with the origin of two flower varieties in Cymbidium . Here, we characterized and analyzed two AG lineage paralogues, CsAG1 and CsAG2, from Cymbidium sinense, both of which were highly expressed in the gynostemium column of a standard C. sinense . Interestingly, we detected ectopic expression of CsAG1 rather than CsAG2 in all floral organs of a stamenoid-tepal variety and significant down-regulation of CsAG1 in a variety with multiple tepals. Over-expression of CsAG1 in wild type Arabidopsis resulted in petal-to-stamen homeotic conversion, suggesting a conserved C-function of CsAG1 in the development of Cymbidium flower. Altogether, our results supported a hypothesis that disruption of a single AG -like factor would be associated with the formation of two domesticated varieties in C. sinense . Floral development: How the plum blossom orchid got its shape: A single gene underlies the remarkable differences between the flowers of two varieties of the popular orchid Cymbidium sinense . Orchid flowers are highly specialized, with many unique flower structures. Although the genetics of flower development have been well-studied, they are not as well understood in orchids. Xia Huang at Sun Yat-sen University in China and coworkers studied the genetics underlying differences between a standard C. sinense flower and a flower of the "Ling-Nan-Da-Mei" or plum-blossom variety, in which the tepals (the outer petal-like structures) strongly resemble stamens (which produce pollen). They found that in the "Ling-Nan-Da-Mei" flowers, a gene that controls stamen development is also switched on in the tepals, giving them a more stamen-like shape. Studying how genetic changes affect flower form can illuminate how so many different types of flowers evolved.